0374 Markers for Hypnotic Abuse Liability: Cortisol in Insomnia?. (27th April 2018) - Roehrs, T; Koshorek, G; Withrow, D; Roth, T
Abstract: Introduction: It is hypothesized that stress increases vulnerability to drug abuse. Some insomniacs show hyperarousal by increased physiological responses to stress, elevated alertness on the Multiple Sleep Latency Test (MSLT) and elevated diurnal NE concurrent with the MSLT elevation. Studies have reported cortisol elevation before sleep in insomnia vs controls. We sought to determine whether cortisol levels, both diurnal and pre-sleep, would vary as a function of MSLT and thus potentially serve as markers for hypnotic abuse liability. Methods: DSM-IVR diagnosed insomniacs (N=110), aged 32–65 yrs, having no other sleep disorder, unstable medial or psychiatric diseases or drug dependency served as subjects. On a screening MSLT 26 had MSLTs < 10 min (Lo) and 44 ≥15 min (Hi). Participants took 10mg zolpidem or placebo, double-blind, nightly for 12 months. In months 1, 4, 8 and 12, urine was collected over 24 hrs in 8 hr- aliquots and assayed for cortisol (Ward Laboratories, Ann Arbor, MI). Saliva samples were collected 35 min before bedtime and drug administration in month 1 and 8, analyzed for cortisol levels (Salimetrics, State College, PA), and compared to a non-insomnia group (N=41). Results: Pre-sleep salivary cortisol was higher in insomniacs than controls (2.23+/-2.12 vs 1.49+/-0.91 ug/L, p<.01), but did not differ as a function of MSLT. Nightly zolpidem reduced pre-sleep cortisol relative to placebo on month1, Zol:1.51+/0.87 vs Pbo:1.79+/1.44 and month 8, Zol:1.52+/0.80 vs Pbo:1.94+/1.48 ug/L, (p<.02) with no months effects. Daytime (0700-1500 hrs) urinary cortisol was higher overall in the Hi vs Lo MSLT insomniacs (Hi: 18.6+/-10.9 vs Lo: 12.9+/-7.1 ug/L, p<.04), was stable across months, and was not reduced with zolpidem. In self-administration assessments those with Hi MSLT increased the number of capsules (zolpidem or placebo) chosen over the 12 months. Conclusion: Hyperarousal (MSLT) is associated with higher daytime urinary cortisol levels and increased drug seeking. This suggests that Hi MSLT and its correlate elevated cortisol may be a potential hypnotic abuse marker among insomniacs. Support (If Any): NIDA, grant#: R01DA17355 awarded to Dr. Roehrs.